The Relevance of Inquiry-Based Learning in Basic Reading Skills Exercises for Improving Student Learning Outcomes in Madrasah Ibtidaiyah - Aslan Aslan (AT-TAJDID, 2021)
This study discussed inquiry-based learning activities in reading skills training students in Madrasah Ibtidayah and elementary schools in Indonesia. In learning to understand according to Islam, reading skills receive special attention from other skills such as speaking, listening, and writing skills. Get an understanding and application of strengthening reading learning that can be started from the elementary school level, and this theme will be discussed with the literature review method from national and international journal publications. A descriptive qualitative design study will be a method of analyzing a series of data. The review process involves a phenomenological approach, coding systems, and critical evaluation to produce data findings to answer our research themes that meet the findings' validity and reliability. Finally, we can conclude our findings, among others, that the ten publications and literature have confirmed that the application of inquiry-based learning approaches is very relevant to be applied in the learning environment of elementary madrasah schools. Thus these findings will be useful to whichever party